Discourse analysis investigating processes of social construction - Phillips, Nelson. (Qualitative research methods ;, 2002)
'Discourse Analysis: Investigating Processes of Social Construction' reflects on the practice of analyzing discourse and the potential for revealing the processes of social construction that constitute social and organizational life.